The Impacts of Fundamental and Macroeconomic Factors on the Stock Price of Oil Palm Plantation Companies in Indonesia Stock Exchange (IDX) - Resi Ayudya; Anik Suwandari; Rudi Hartadi (Universitas Hayam Wuruk Perbanas, 2017)
The oil palm plantation companies in this study were the selected companies listed on the Indonesia Stock Exchange. This study aimed to determine the impacts of fundamental and macroeconomic factors on the stock price of the oil palm plantation companies in IDX. The determination of the research area was based on the designed method (purposive sampling) consisting of PT Astra Agro Lestari Tbk, PT PP London Sumatra Indonesia Tbk, and PT Tunas Baru Lampung Tbk. The data was collected using literature review method with secondary data sources in the form of time series data of stock prices, fundamental and macroeconomic factors in the period from January 2006 up to June 2016. The results of this study indicated that the movement of stock prices of oil palm plantations in Indonesia Stock Exchange was influenced by the fundamental and macroeconomic factors which consist of ROE (Return on Equity) with a regression coefficient of -133.35, DER (Debt to Equity Ratio) with a regression coefficient of -26.37, and EPS (Earning per Share) with a regression coefficient of 15.47. The macroeconomic factors consist of Rupiah exchange rate with a regression coefficient of -0273 and the CPO (Crude Palm Oil) price with a regression coefficient of 0.859. For the investors, they can consider the overall internal and external factors, which are based on the company's financial ratios and macroeconomic conditions.